MicroRNoma do carcinoma de pâncreas - Felix, Tainara Francini [UNESP] (2016)
Background: Genetic alterations were previously identified and associated with the development and progression of pancreatic carcinoma, however, identification of such alterations has not been currently used for the development of efficient treatment strategies. Therefore, the identification of other genetic and epigenetic changes, such as alterations in non-coding RNA molecules is urgently needed for the development of novel therapies. Recent studies have suggested that microRNAs (miRNAs) are frequently deregulated in several carcinomas and may contribute in the several steps of development and tumor progression. Global miRNA profiling analysis in pancreatic carcinoma and the identification of miRNA target genes may lead to new avenues for the identification of clinically applicable biomarkers. Objectives: To identify global microRNA (miRNA) expression profiles and miRNA predicted target genes in pancreatic carcinoma. Patients and Methods: 30 formalin fixed, paraffin embedded (FFPE) pancreatic carcinoma tissue samples were used, including 24 pancreatic ductal adenocarcinoma (PDAC) and 6 adenocarcinomas of Vater papilla (AMP) and their paired histologically adjacent normal tissues. Global miRNA expression profiles were determined using the TaqMan Array Human MicroRNA Cards (TLDA) (card A, v3.0) (Life Technologies) platform. Data analysis used the ExpressionSuite Software v1.0.3. Statistical analysis was performed to correlate miRNA expression with relevant clinical data, using SAS 9.3 software. Computational bioinformatic analysis was performed to identify predicted miRNA target genes, as well as protein-protein interaction networks and miRNA-mRNA molecular pathways. Results: We identified 63 significantly deregulated (significantly deregulated is herein defined as FC≥2 and p<0.05) miRNAs in PDAC (33 over-expressed and 30 under-expressed) compared to paired histologically normal pancreatic tissue. In AMP, a group of 7 miRNAs was significantly deregulated (4 over-expressed and 3 under-expressed) compared to normal. Our results showed a complexity of miRNAs changes potentially associated to PDAC tumorigenesis. Interestingly, 3/7 miRNAs were commonly deregulated in PDAC and AMP tumors. Discussion: Global miRNA expression profiles identified in PDAC and AMP showed that PDAC have a significantly higher number of altered miRNAs and consequently, a higher number of predicted miRNA target genes than AMP, which could be potentially associated to disease progression and tumor aggressiveness in PDAC compared to AMP. Commonly deregulated miRNAs in PDAC and AMP suggest that common molecular pathways may be deregulated in these two histological subtypes of pancreatic carcinoma. Among the miRNAs exclusively deregulated in PDAC, we identified several predicted miRNA target genes associated to tumor invasion and metastasis and poor prognosis of patients with cancer. Conclusion: miRNAs identified herein may be associated to the biology of PDAC and AMP. Functional validation studies are required to elucidate the role of miRNAs as modulators of oncogenesis mechanisms in PDAC and AMP.